2018
DOI: 10.1016/j.ejvs.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Combined Impact of Chronic Kidney Disease and Contrast Induced Acute Kidney Injury on Long-term Outcomes in Patients with Acute Lower Limb Ischaemia

Abstract: In patients with ALI undergoing lower limb revascularisation, both CKD and CI-AKI were significantly associated with poor long-term outcomes compared with either CKD or CI-AKI alone. Further studies are required to assess this association and to confirm the combined effect of CKD and CI-AKI on long-term clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Following the current recommendations, indications for revascularization in CKD patients with PAD did not differ from those applied to patients without CKD. 60 Such an attitude is compatible with the result of a large study enrolling 351 patients who underwent either surgical or percutaneous revascularization for CLI. 61 This analysis has been assessed on patients with different levels of renal function impairment and showed that revascularization conferred benefits in terms of amputation-free survival and limb salvage in both CKD and non-CKD patients.…”
Section: Why Does Ckd Affect the Management And Prognosis Of Pad?mentioning
confidence: 56%
See 2 more Smart Citations
“…Following the current recommendations, indications for revascularization in CKD patients with PAD did not differ from those applied to patients without CKD. 60 Such an attitude is compatible with the result of a large study enrolling 351 patients who underwent either surgical or percutaneous revascularization for CLI. 61 This analysis has been assessed on patients with different levels of renal function impairment and showed that revascularization conferred benefits in terms of amputation-free survival and limb salvage in both CKD and non-CKD patients.…”
Section: Why Does Ckd Affect the Management And Prognosis Of Pad?mentioning
confidence: 56%
“… 60 With respect to perioperative complications, CKD patients were found at increased risk of respiratory insufficiency, intubation, bleeding and infectious. 60 , 71 …”
Section: Why Does Ckd Affect the Management And Prognosis Of Pad?mentioning
confidence: 99%
See 1 more Smart Citation
“…46 In a large cohort of 1 017 patients treated for ALI there was an association between contrast induced acute kidney injury and increased all cause mortality, but there were multiple potential confounders associated with comorbidities. 47 Anatomical coverage usually extends from just cranial to the origins of the renal arteries down to the feet, with an average scan length of around 120 cm. If the distal vessels are not well opacified (e.g., in the case of femoropopliteal aneurysm or slow flow in the setting of cardiac failure), a secondary acquisition may be necessary.…”
Section: 23mentioning
confidence: 99%
“…Patients undergoing percutaneous peripheral revascularization, in particular patients with acute or critical ischemia of the lower limbs, represent a particularly fragile population often with significant comorbidity. In these patients the onset of CI-AKI is also associated with a significant increase in mortality (Zlatanovic et al, 2018). The different definitions of CI-AKI used and the heterogeneity of patients with peripheral atheroma undergoing angiographic procedures and percutaneous revascularization, complicate reliable epidemiological analysis.…”
Section: Clinical-epidemiological Impact Of Ci-akimentioning
confidence: 99%